FEATURES OF NEUROPROTECTIVE TREATMENT OF CHILDREN WITH PRIMARY CONGENITAL GLAUCOMA - З. Назирова; Д. Туракулова (Bukovynian State Medical University, 2023)
Normalization of intraocular pressure is an indispensable condition, but it does not guarantee stabilization of the glaucomatous process. Neuroprotective therapy aimed at maintaining the active function of axons of ganglion cells is of great importance. The aim of the study was to study the eff ectiveness of the neuroprotective eff ect of the Cortexin drug in congenital glaucoma. Material and methods. Thirty-two (64 eyes) children with congenital glaucoma in the compensation stage were included in the study. Of these, 18 children (36 eyes) were included in the main group that received the neuroprotectant Cortexin. The remaining 14 children (28 eyes) were included in the control group and received standard treatment. Research methods: Visometry, ophthalmoscopy, perimetry, tonometry, tonography, ocular ultrasound, gonioscopy. Results. All patients underwent antiglaucomatous surgery and, in the absence of negative dynamics during the year, neuroprotective treatment with Cortexin was performed every three months. To study visual acuity in young children, a computer program was developed and used to determine visual acuity. The computer program «Scale for assessment of visual functions» was certifi ed (No. DGU 11841). Next, the parents of the child were explained how to score. After 1 month and after 3 months of treatment, the parents fi lled in the table and deducted points. After completion of neuroprotective treatment within one year, we collected data from the questionnaire fi lled out by the parents and analyzed visual acuity. Data analysis in the main group showed an increase in visual acuity in all stages of glaucoma except the fi nal stage. In children in the control group, visual acuity before surgery was identical to that in the main group. After one year of observation, the increase in visual acuity in the control group was much less than in the main group. Conclusion. Thus, the dynamics of visual acuity improvement was signifi cantly more pronounced in the main group, which indicates the usefulness of including drugs with neuroprotective eff ect in the complex treatment of glaucomatous neuropathy.